Women key to successful democracy - Janapathy, Varalakshmi (Delhi : Kalpaz Publications, 2009)
In Indian context.
Includes index.
Keywords: Women -- Political activity -- India; Equality -- India; Women in development -- Government policy -- India; Local government -- India